New Soliton Solutions for the Higher-Dimensional Non-Local Ito Equation - İnç, Mustafa; Az-Zo'bi, E. A.; Jhangeer, Adil; Rezazadeh, Hadi; Ali, Muhammad Nasir; Kaabar, Mohammed K. A. (De Gruyter Poland Sp Z O O, 2021)
In this article, (2+1)-dimensional Ito equation that models waves motion on shallow water surfaces is analyzed for exact analytic solutions. Two reliable techniques involving the simplest equation and modified simplest equation algorithms are utilized to find exact solutions of the considered equation involving bright solitons, singular periodic solitons, and singular bright solitons. These solutions are also described graphically while taking suitable values of free parameters. The applied algorithms are effective and convenient in handling the solution process for Ito equation that appears in many phenomena.
Keywords: Partial differential equation; Ito equation; Simplest equation method; Soliton; Traveling wave solution